STUDI EKSPLORASI TENTANG KESIAPAN PEMERINTAH KOTA SURABAYA MENUJU PENERAPAN AKUNTANSI AKRUAL - Anggraeni, Gresi Ayu; Riharjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThe purpose of this research is to find out the readiness of the municipal government in the implementation ofaccrual accounting. And, to find out what sort of constraints that are encountered by Surabaya municipalgovernment, and to find out what sort of acceleration strategies that has been implemented by Surabayamunicipal government in order to overcome them. This research is a descriptive research. Observation,documentation, and interview method through an oral question to the research subject are used as the datacollection technique. The result of the research of the readiness of Surabaya municipal government in theimplementation of accrual accounting shows that Surabaya municipal government has not completelyimplemented the accrual based accounting. Some Regional Working Units of Surabaya city is stillimplementing the cash based accounting going to accrual based. The acceleration strategy that has already beenimplemented is used to overcome the constraints, and it is used as the acceleration of the implementation processof accrual based accounting completely.Keywords: Accrual accounting, readiness, obstacle, acceleration strategy.